2022
DOI: 10.20944/preprints202201.0211.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Spermidine Synthase Gene SPD1: A Novel Auxotrophic Marker for Chlamydomonas Reinhardtii Designed by Enhanced CRISPR/Cas9 Gene Editing

Abstract: Biotechnological application of the green microalga Chlamydomonas reinhardtii hinges on the availability of selectable markers for effective expression of multiple transgenes. However, biological safety concerns limit the establishment of new antibiotic resistance genes and until today, only few auxotrophic markers exist for C. reinhardtii. The recent improvements in gene editing via CRISPR/Cas9 allows directed exploration of new endogenous selectable markers. Since editing frequencies with CRISPR/Cas9 techniq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Previous reports have demonstrated that multiple fluorescent proteins can be combined in the alga cell simultaneously by transformation and mating using micro-plate readers and confocal microscopy imaging techniques (Rasala et al, 2013(Rasala et al, , 2014. FP expression can also screened at the agar-plate level with whole-plant or stereo-microscopy imaging apparatus, a technique which assists selection of robust expressing cell lines quickly from a population (Lauersen et al, 2016(Lauersen et al, , 2018Wichmann et al, 2018;Freudenberg et al, 2021Freudenberg et al, , 2022aFreudenberg et al, , 2022b. Fluorescent proteins are not the only bio-molecules which emit some amount of fluorescence signal in host cells and tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that multiple fluorescent proteins can be combined in the alga cell simultaneously by transformation and mating using micro-plate readers and confocal microscopy imaging techniques (Rasala et al, 2013(Rasala et al, , 2014. FP expression can also screened at the agar-plate level with whole-plant or stereo-microscopy imaging apparatus, a technique which assists selection of robust expressing cell lines quickly from a population (Lauersen et al, 2016(Lauersen et al, , 2018Wichmann et al, 2018;Freudenberg et al, 2021Freudenberg et al, , 2022aFreudenberg et al, , 2022b. Fluorescent proteins are not the only bio-molecules which emit some amount of fluorescence signal in host cells and tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic fusion of target recombinant proteins with FPs has become a common strategy to identify high transgene expressing transformants in a population and facilitate genetic/metabolic engineering concepts with C. reinhardtii (Lauersen et al, 2016(Lauersen et al, , 2018Wichmann et al, 2018;Perozeni, 2020;Einhaus et al, 2022;Freudenberg et al, 2021;Freudenberg et al, 2022a). Target protein-FP fusions allow rapid identification of cell lines exhibiting robust transgene expression and translation as stronger fluorescence signal correlates to higher abundance of target-fusion protein products.…”
Section: Introductionmentioning
confidence: 99%